2019
DOI: 10.5812/archcid.64282
|View full text |Cite
|
Sign up to set email alerts
|

Study on Knowledge, Attitude and Practice of Health Workers of East Azerbaijan, Ilam and Khorasan Razavi Provinces about Leishmaniasis During 2015 - 2016: A Comparative Study Before and After Intervention

Abstract: Background: Leishmaniasis is a parasitic infection caused by the Leishmania spp. and transmitted via the bite of infected female Phlebotomine sand flies. Health education is one of the important approaches to increasing knowledge and awareness of the community about leishmaniasis health issues. Objectives: The aim of this study was to assess the effect of health education on knowledge, attitude and practice (KAP) of health volunteers about leishmaniasis in some areas endemic for cutaneous and visceral leishman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…This study identified misconceptions regarding basic clinical and epidemiological topics on VL among PHC professionals from the municipality of Rondonopolis, which was consistent with previous investigations conducted in Brazil 4 and abroad 13 . In contrast with other studies, we performed a health training intervention, which has positively influenced the basic knowledge on VL.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…This study identified misconceptions regarding basic clinical and epidemiological topics on VL among PHC professionals from the municipality of Rondonopolis, which was consistent with previous investigations conducted in Brazil 4 and abroad 13 . In contrast with other studies, we performed a health training intervention, which has positively influenced the basic knowledge on VL.…”
supporting
confidence: 90%
“…The positive impact of health training on the basic knowledge of PHC professionals on VL was already demonstrated in India 13 . In our study, the individuals became more aware of the early more frequent clinical signs of human VL.…”
mentioning
confidence: 94%
“…In Waziristan, a large proportion of participants were reported to be using bed nets and insecticides as preventive measures against cutaneous leishmaniasis [ 27 ]. Health education can bring awareness to the community at risk and thus, can be helpful in the prevention of the disease at the individual and community levels [ 43 ]. Most participants were not aware of the sandfly as a vector for leishmaniasis and a similar trend was reported by Akram et al, 2015 [ 26 ] where 84.0% of the respondents were unable to identify the transmission of cutaneous leishmaniasis by the sandfly.…”
Section: Discussionmentioning
confidence: 99%
“…The number of participants in each study ranged from 20 to 450 people, with a total of 2050 participants across all 13 studies. These participants included residents of the region (Reis et al 2006), students (Ghodsi et al 2019;Motamedi et al 2010;Saghafipour et al 2017), health-related personnel (Kashfi et al 2012;Dehghani-Tafti et al 2011), volunteer health workers (Hazavehei et al 2014;Zeinali et al 2019), mothers (Baghianimoghadam et al 2016;Kavoosi and Shojaeizadeh 2016), housewives (Jeihooni et al 2019;Nazari et al 2016), andparents (Dehghani-Tafti et al 2017). Although the interventions were delivered primarily to these target populations, in five studies, intervention delivery was also aimed at a further secondary group made up of people considered to be influential in the community, including family members, health staff, teachers, and local dignitaries (Ghodsi et al 2019;Hazavehei et al 2014;Jeihooni et al 2019;Kashfi et al 2012;Motamedi et al 2010).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Various health education activities were used in the interventions, including lectures, slideshows, videos, banners and/or posters, group discussions, demonstrations, Question and Answer sessions, brainstorming, role-playing, thematic workshops, and distributions of pamphlets, booklets, and manuals. The most commonly used were lectures, adopted in eight interventions (Baghianimoghadam et al 2016;Ghodsi et al 2019;Jeihooni et al 2019;Kavoosi and Shojaeizadeh 2016;Motamedi et al 2010;Nazari et al 2016;Dehghani-Tafti et al 2011;Zeinali et al 2019) and group discussions (Baghianimoghadam et al 2016;Ghodsi et al 2019;Jeihooni et al 2019;Kavoosi and Shojaeizadeh 2016;Motamedi et al 2010;Nazari et al 2016;Saghafipour et al 2017) which were used in six interventions, across the thirteen studies. Overall, each intervention combined multiple educational activities, with the exception of Reis et al's (2006) intervention, which was only based on thematic workshops.…”
Section: Characteristics Of Interventionsmentioning
confidence: 99%